Subtherapeutic lithium supplementation causes physiological eccentric cardiac hypertrophy in young‐adult wild‐type male mice - Sophie I. Hamstra; Mia S. Geromella; Peter Tiidus; Panagiota Klentrou; Rebecca E. K. MacPherson; Val A. Fajardo (Physiological Reports)
Abstract Six weeks of low‐dose lithium (Li) supplementation has been shown to improve the activity of cardiac sarco(endo)plasmic reticulum calcium (Ca2+)‐ATPase (SERCA) in C57BL/6J wild‐type (WT) male mice. Improvements in myocardial SERCA function can lead to improvements in systolic and diastolic function in various rodent models. In this study, we tested the hypothesis that 12 weeks of subtherapeutic Li supplementation (10 mg/kg/day) would enhance SERCA function and positively influence cardiac contractility and morphology. Cardiac function and morphology were assessed using high‐frequency ultrasound in the final week of Li treatment. Subsequently, SERCA activity, Ca2+ uptake assays, and Western blotting for glycogen synthase kinase‐3β, SERCA2, and its inhibitor phospholamban (PLN) were performed on isolated left ventricle tissue. After 12 weeks of subtherapeutic Li supplementation, the heart underwent eccentric remodeling, exhibited by increased left ventricle internal diameter and volumes during systole and diastole, ultimately leading to greater stroke volume. However, we did not find any specific alterations in systolic or diastolic functional measures; nor were there any changes in SERCA activity and its content relative to PLN after Li supplementation. Thus, while Li supplementation appears to positively influence cardiac morphology to increase stroke volume, these changes are independent of changes to SERCA function.